Sprayable Bonded Fabric with Protective Chemical and Biological Properties - V. V. Zavyalov; M. P. Shabelnikov; E. U. Basova; N. V. Zavyalova; V. A. Kovtun; V. I. Kholstov (Вестник войск РХБ защиты, 2025)
It is possible to create self-assembling smart spray materials with preset protective chemical and biological properties by modifying the liquid fabrics composition.Relevance. Previous “smart” sprayed fabrics didn’t possess protective chemical and biological properties. However due to liquid base modification the mentioned fabrics acquire these properties, and if we spray them on clothes, uniform and equipment they can save life of soldiers and military vehicles.The purpose of the study is to explain and justify the process of creation of protective materials from liquid fabrics and to prove that it is possible to create fabrics with set properties of autopurification and self-sanitizing. Study base sources. Scientific publications available on the Internet and own studies of the authors of this paper.Materials and methods. Analytical method has been employed in this study.Results. The authors have provide a theoretical justification for the possibility of creation of smart self-assembling protective materials with set properties of autopurification and self-sanitizing. It has been proved that the spray can create any clothes for any purpose. We can give new properties to such clothes, if we perform liquid base modification with special additives. When we create such self-assembling bonded fabric, it doesn’t require special preparation, sewing and storage in special conditions. The novelty is that we create a liquid suspension that contains nanofibers of fabrics, water, tetrafluoroethane (or other gas), hydrocarbon solvent, pigment colourant nanoparticles of metals and nano-sized, enzymatic polyelectrolyte complexes. This liquid suspension, when sprayed will turn to an innovative smart fabric that will be able to protect from pathogenic microorganisms and toxic chemicals.Conclusions. (1) “Smart” liquid innovative fabrics and clothes are quite promising for national security protection and national defense. (2) The authors suggested that the existing compositions of liquid fabric sprays should be modified. The added chemical and biological active components will give the “smart” fabrics in question such properties as self-assembly, autopurification and self-sanitizing. (3) The choice of the components for a new composition for liquid fabrics has been justified in this article.